Factors influencing the Disbursements of Loans from selected Commercial Banks to Small-scale and Medium-scale Agro-based Enterprises in Imo State, Nigeria - Chidiebere-Mark Nneka Maris; Oguoma Nicolas; Onyeneke Robert Ugochukwu; Henri-Ukoha Ada (Agricultura Tropica et Subtropica, 2014)
This study evaluated the performance of small and medium-scale agro-based enterprises financed by selected commercial banks in Imo State, Nigeria. It identified the dominant agro-based enterprises in the study area; estimated the adequacy of funds disbursed to them by selected commercial banks; determined factors that influenced the disbursements and the relative risk in financing them. A combination of purposive and random sampling techniques was adopted in selecting the respondents (commercial banks and small scale and medium scale agro-based enterprises) for the study. Questionnaire and interview schedule were the main tools for data collection and data collected were analyzed using descriptive and econometric tools. The result showed that the mean amount disbursed to small-scale agro-based enterprises was N533, 833.33 ($3558.89) while a mean of N1, 813,021 ($12086.81) was disbursed to the medium scale enterprises. The multiple regression coefficient for interest rate (X3), experience (X4) and repayment rate(X6) were positive and significant at 1% while category of enterprise (X5) was negative and significant at 5% implying that these variables are important factors influencing the amount of loan disbursed to small-scale agro-based enterprises in Imo State while interests rate (X3) and repayment rate (X6) were positive and significant at 1% ; coefficient for age (X2), experience (X4) and category of enterprise (X5) were negative and significant at 5%, implying that these variables are important factors influencing the amount of loan disbursed to medium scale agro-based enterprises in the study area. The risk in financing medium-scale agrobased enterprises was higher than that for the small-scale agro-based enterprises. The main constraints faced by agro-based SMEs in obtaining loans were mainly insufficient collateral (100%), and high interest rate (87.45%). It is therefore recommended that commercial banks should make more credit accessible to agro-based SMEs and at better conditions and cheaper lending rate to encourage their increased production and expansion